2020
DOI: 10.3390/en13061327
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Turbine Cycles with Organic Media

Abstract: Organic Rankine Cycle (ORC) power plants have become very popular and have found their applications in systems with renewable sources of energy. So far their overall efficiencies are not very impressive and only for the upper temperature of about 300 °C do they exceed 20%. A drawback of these cycles is the limitation of the cycle upper temperature due to the heat exchanger technology and the materials used. However, it is possible to overcome these difficulties by certain modifications of the thermodynamic cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…For power plants with isothermal turbines, this growth is as high as 3.6 points for c3cc6 up to 10.1 percent points for R1233zd. The comparison of the efficiency for power plants with isothermal and adiabatic expansion is presented in Figure 9 for subcritical live vapor parameters [19] and in Figure 10 for supercritical parameters.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For power plants with isothermal turbines, this growth is as high as 3.6 points for c3cc6 up to 10.1 percent points for R1233zd. The comparison of the efficiency for power plants with isothermal and adiabatic expansion is presented in Figure 9 for subcritical live vapor parameters [19] and in Figure 10 for supercritical parameters.…”
Section: Resultsmentioning
confidence: 99%
“…For power plants with isothermal turbines, this growth is as high as 3.6 points for c3cc6 up to 10.1 percent points for R1233zd. The comparison of the efficiency for power plants with isothermal and adiabatic expansion is presented in Figure 9 for subcritical live vapor parameters [19] and in Figure 10 for supercritical parameters. In the case of supercritical parameters, due to a higher value of the initial pressure, we observe higher cycle efficiency than for the power plants with subcritical parameters.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…20% [25]. It is possible to improve the cycle efficiency by increasing the upper temperature and modifying the plant design [26,27]. Despite very considerable developments in distributed energy and alternative energy sources, it should be concluded that high-efficiency power plants with steam turbines set to supercritical parameters, combined gas-steam cycle power plants, and nuclear power plants [28] will be developed in terms of high installed capacities.…”
Section: Introductionmentioning
confidence: 99%